RANCANG BANGUN MESIN CNC UKIR KAYU DENGAN 3 SUMBU MENGGUNAKAN MIKROKONTROLLER : RANCANG BANGUN MESIN CNC UKIR KAYU DENGAN 3 SUMBU MENGGUNAKAN MIKROKONTROLLER - Fashiha Ilman, Abdillah (Politeknik Negeri Madura, 2022)
The Abstract — The development of technology in the current era is growing rapidly, one of its uses is to be able to help industrial processes on a small or large scale. One technology that is developing rapidly is the CNC Wood carving machine. The problems that often arise in the process of the furniture industry are the limited number of workers with large orders. Therefore, in this study designing a CNC wood carving machine with 3 axes using a microcontroller as one way out to overcome these problems. The three x, y, z axes on the equipment will move in an orderly manner according to the code that has been made previously, using a stepper motor controlled by a microcontroller. while for the engraving process using a Wood Trimmer M-2700 motor. This equipment is still in prototype form which has dimensions of 80 cm x 60 cm and a maximum work area of ??30 cm x 30 cm. This equipment utilizes a code to command the machine to perform engraving automatically. The code is obtained from an image that has been designed and then converted to G-code through the Aspire 9.0 software. This machine is capable of engraving with the smallest size of 2 mm. The engraving process can be carried out at a speed of 0.62 cm/s and the measurement has an error rate of below 5%. This research can be developed so that it can help and encourage the process of the furniture industry in the wider community. Keywords: CNC, G-Code, Microcontroller, Stepper Motor, Wood Trimmer M-2700